2022
DOI: 10.1590/1517-8692202228042020_0131
|View full text |Cite
|
Sign up to set email alerts
|

Mood States and Quality of Life in Paralympic Boccia Athletes in the Covid-19 Pandemic

Abstract: Introduction: Although studies have been conducted in the athlete population during the pandemic, its impacts on Paralympic athletes are still unknown. Objective: To evaluate the mood and quality of life of Paralympic boccia players during the COVID-19 pandemic period. Method: Questionnaires assessing mood, quality of life, and demographic data were sent electronically via social media. The study included 43 athletes from all functional classes (BC1 = 8, BC2 = 12, BC3 = 11, and BC4 = 11) and four regions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…Importante ressaltar que muitos locais de esportes fecharam durante a pandemia e as pessoas tiveram menos oportunidades de comunicação ao ar livre, de comunicação externa, e em decorrência disso, muitas pessoas, inclusive os atletas tiveram que praticar esportes em casa porque havia o medo de infecções cruzadas (Arruda et al, 2023;Rangel Colmenero, 2023), o que fez com que o entusiasmo das atividades esportivas em grupo diminuísse gradualmente (Camargo-Junior et al, 2020), gerando grandes consequências para a saúde mental, como ansiedade e depressão. Com isso, o papel dos treinadores ganhava ainda mais importância ao ter que, além de se manterem motivados, reinventarem os treinamentos de suas atletas, para que elas também se mantivessem motivadas, e ao mesmo tempo em que estavam isoladas fisicamente, não estivessem tão distantes da sua profissão e prática esportiva.…”
Section: Discussionunclassified
“…Importante ressaltar que muitos locais de esportes fecharam durante a pandemia e as pessoas tiveram menos oportunidades de comunicação ao ar livre, de comunicação externa, e em decorrência disso, muitas pessoas, inclusive os atletas tiveram que praticar esportes em casa porque havia o medo de infecções cruzadas (Arruda et al, 2023;Rangel Colmenero, 2023), o que fez com que o entusiasmo das atividades esportivas em grupo diminuísse gradualmente (Camargo-Junior et al, 2020), gerando grandes consequências para a saúde mental, como ansiedade e depressão. Com isso, o papel dos treinadores ganhava ainda mais importância ao ter que, além de se manterem motivados, reinventarem os treinamentos de suas atletas, para que elas também se mantivessem motivadas, e ao mesmo tempo em que estavam isoladas fisicamente, não estivessem tão distantes da sua profissão e prática esportiva.…”
Section: Discussionunclassified
“…Due to the high physical and psychological demands of the routines that Paralympic athletes engage in, good sleep quality is necessary for an efficient recovery [11]. However, due to the restrictions imposed by the COV-ID-19 pandemic, the scientific literature does not report information for this context, since the SARS-CoV-2 virus imposed the need to adhere to strategies such as social distancing and cancellation of events [12]. Despite the limited information, investigations have found that the COVID-19 pandemic caused significant effects on the behavior of Paralympic athletes who were on their way to Tokyo, as well as stress and changes in their training patterns [13].…”
Section: Introductionmentioning
confidence: 99%
“…Before the pandemic, only the study by Barak et al (2016) investigated the effect of playing boules independently or dependent on the use of aids on psychological aspects, including mood and quality of life. More recently, Arruda et al (2022) explored the possible influence of social isolation in these aspects in players of this sport, with greater influence on functional classes BC4 and BC2, with athletes from the Northeast region of Brazil presenting lower indicators of quality of life oriented towards the environment.…”
Section: Introductionmentioning
confidence: 99%